A hybrid parallel algorithm for large sparse linear systems. Issue 6 (29th August 2018) - Rao, S. Chandra Sekhara; Kamra, Rabia
Summary: Large sparse linear systems arise in many areas of scientific computing, and the solution of these systems is the most time‐consuming part in many large‐scale problems. We present a hybrid parallel algorithm, named incomplete W Z parallel solver (IWZPS), for the solution of large sparse nonsingular diagonally dominant linear systems on distributed memory architectures. The method is a combination of both direct and iterative techniques. We compare the present hybrid parallel sparse algorithm IWZPS with the direct and iterative sparse solvers, namely, MUMPS and ILUPACK, respectively. In addition, we compare it with a hybrid parallel solver, DDPS.